Karakteristika dan Khasiat Daun Keladi Tikus (Typhonium divaricatum (L.) Decne) Iradiasi - Katrin, Ermin; Novagusda, Fahrul Nizar; Susanto,; Winarno, Hendig (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
Keladi Tikus (Typhonium divaricatum (L.) Decne), Araceae, is one ofIndonesia plants that can inhibit cancer cell growth. Preservation techniques of herbalmedicine using gamma irradiation has long been used to prolong shelf life, but only a littlescientific data that study the effect of irradiation on the properties of them. In this studyirradiation of keladi tikus leaves with a dose of 0, 5, 7.5, 10 and 15 kGy, followed bymaceration of each with n-hexane, ethyl acetate and ethanol, respectively. Effects of gammairradiation were studied by testing the inhibitory activity against the L1210 leukemia cell forthe extracts, fractionation by column chromatography, analysis by TLC, spectrophotometerand HPLC. The result of cytotoxicity test against L1210 leukemia cells showed that the ethylacetate extract of the most active potential as anticancer IC50 value respectively 11.81 μg/ml.Result of fractionation of ethyl acetate extract were obtained by column chromatography with6 fractions. Fraction 2 was the most active fraction with the lowest IC50 value of 4.14 μg/ml. Gamma irradiation dose of 15 kGy reduced the cytotoxic activity of fraction 2 against L1210leukemia cells, but still within the active potent (IC50 values ≤ 20 μg/ml) as an inhibitor to thegrowth of leukemia L1210. Based on the cytotoxicity data, profiles of TLC, UV-VIS spectrumand HPLC between control and irradiated samples showed that the maximum dose forirradiation of keladi tikus leaves was 7.5 kGy.